The convergence between the Yezidi and the Yarsan (Ahl-e Haqq) religions in historical, traditional, and religious aspects - Dr. Zhilwan Abdullah Ahmed (Journal of College of Education, 2025)
Kurdistan, since ancient times, has been the home of many different religious and ethnic components. those who formed a Kurdish community with diversity ethnic and religious in the region. In that context, both of the Yezidi and Kakai communities, who are composed of old sects in Kurdish society, and they had an important role in the cultural and religious field. They have been a part of the structure of the ancient and modern Civilization of Iraqi and Kurdish society. Both religions have several similarities and differences points, and they were living in two important areas in Kurdistan and they defended themselves during the past conflicts. This research consists of four chapters:In the first chapter, we talked about the history of the appearance of the Yazidi religion and the prominent customs of that religion. In the second chapter, we talked about the history of the appearance of the Kaki religion and their symbols and traditions. And in the third chapter, we talked about the comparison between the two prominent Iraqi religions and we identified the similar points between them. And in the fourth chapter, which is the last chapter, we discussed the different points between the both religions, and in the end, we pointed out the conclusion and the important sources that we benefited from in this research.